Pengaruh Budaya Organisasi terhadap Kinerja Karyawan melalui Mediasi Work Life Balance dan Kepuasan Kerja pada Karyawan Bank Sultra Cabang Raha - Wa Ode Sitti Rahma Sari; Nasrul Nasrul; Salma Saleh (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The purpose of this study was to examine and explain the influence of organizational culture on employee performance, mediated by work-life balance and job satisfaction at Bank Sultra’s Raha Branch. This study design was based on a quantitative approach with a cross-sectional survey data collection method. Data collection was conducted using a questionnaire instrument. The sample for this study used purposive sampling of 40 employees at Bank Sultra’s Raha Branch. Data analysis used Partial Least Squares (PLS) hypothesis testing. The results showed that organizational culture had a positive and significant effect on work-life balance, job satisfaction, and employee performance. Furthermore, work-life balance had a positive and significant effect on employee performance. Furthermore, job satisfaction was shown to have a positive and significant effect on employee performance. These results also demonstrate that work-life balance and job satisfaction act as partial mediators of the influence of organizational culture on employee performance. This means that organizational culture significantly influences improvements in work-life balance and job satisfaction. Consequently, organizational culture significantly contributes to improved employee performance. Thus, it can be concluded that a positive organizational culture can also significantly contribute to improving employee performance, both directly and through its mediating role in work-life balance and job satisfaction.